Assessment of Kupffer Cell–Specific Contrast-Enhanced Ultrasound for Characterization of Suspicious Malignant Focal Liver Lesions - Kumar, Abhinandan; Laroia, Shalini T.; Arora, Abhishek; Mukund, Amar; Patidar, Yashwant; Babbar, Sushant (Indian Journal of Radiology and Imaging, 2025)
This article aims to assess the diagnostic accuracy of Kupffer cell–specific contrast-enhanced ultrasound (Sonazoid) for characterization of suspicious malignant focal liver lesions and the diagnostic accuracy of Sonazoid in differentiating tumoral thrombosis of the portal vein from bland thrombosis.This was a single-center, prospective, cross-sectional study conducted in the Department of Radiology. Baseline gray-scale ultrasound, along with contrast-enhanced imaging, was performed in patients who met the inclusion criteria. CEUS images were read by two radiologists with an experience of 3 and 15 years, respectively. Interobserver agreement between two observers was calculated. CECT and CEMRI images were read by a third radiologist with an experience of around 7 years; he was also blinded to the histopathology and CEUS results. CECT/CEMRI was taken as a gold standard for HCC (based on the evidence-based practice/AASLD guidelines); for non-HCC lesions, histopathology was taken as a gold standard. Diagnostic accuracy, sensitivity, and positive predictive value (PPV) of CEUS were then calculated with respect to the gold standard. In eight cases included in our study, portal vein thrombosis was present, and so the diagnostic accuracy of CEUS with Sonazoid for differentiating tumoral and bland thrombosis was also calculated.CEUS with Sonazoid has a sensitivity of 90%, an accuracy of 87%, and a PPV of 96% for characterizing focal liver lesions. CEUS with Sonazoid (with respect to histopathology) has a sensitivity of 87.5%, specificity of 87.5%, and diagnostic accuracy of 77.8% for the characterization of lesions. In a limited number of patients included in our study, CEUS had a sensitivity, specificity, negative predictive value, and PPV of 100% for differentiating between tumoral and bland thrombus.CEUS is an excellent modality for differentiating tumoral from bland thrombus, and it can be safely used for lesion characterization in patients where CT/MRI contrast agent is contraindicated. In cases of diagnostic dilemma, CEUS can be used as an alternative modality. Since it is radiation free, it can be used in regular surveillance of high-risk patients.
Keywords: Contrast-enhanced ultrasound; Kupffer cell specific; Sonazoid